Development of alumina microspheres with controlled size and shape by vibrational droplet coagulation. Issue 1 (January 2017) - Pype, J.; Michielsen, B.; Seftel, E.M.; Mullens, S.; Meynen, V.
Abstract: Monodisperse alumina microspheres were shaped by making use of the vibrational droplet coagulation technique. A combination of both physical and chemical parameters provided a flexible basis to widely regulate the size of the microspheres. The controlled granulation is based on a stable alumina suspension containing sodium alginate. The sodium alginate binder is used to coagulate the microspheres jetted into a bath of CaCl2 . Several parameters have been varied to study the impact on the suspension's rheology. This in turn dictates the physical parameters required for controlled shaping by the vibrational droplet coagulation technique. The decomposition of the calcium alginate in the alumina microspheres was monitored during the thermal post processing. In this step, the formation of CaCO3 was revealed, resulting in the presence of CaO during the calcination process. Subsequently, this existence of CaO in the alumina matrix leads to the formation of calcium hexaluminate (CaO·6Al2 O3 ) during sintering.